Role of Red Complex Pathogens in The Development of Cardiovascular Diseases - T. K, HARIPRASATH; PRIYADHARSINI, J. VIJAYASHREE; DEVI, R. GAYATRI (The journal of contemporary issues in business and government, 2020)
The pathophysiology of cardiovascular disease (CVD) includes inflammation which ultimately leads to the development of atherosclerosis and thrombosis. Increasing evidence supports oral infections and in particular the common periodontal diseases, to be associated with CVD development. Periodontal infections are common worldwide and in moderate to mild form in about 35% population according to the World Health Organization. The aim of this study is to present a brief review of recent literature available on the association of red complex pathogens in development of CVD. A brief description of oral bacteria, periodontal diseases, atherosclerosis, underlying pathophysiology has been included. There is growing evidence on the association of periodontal diseases and CVD as given by epidemiological studies. The relationship between periodontal red complex pathogens and CVD deserves further research because of its consequences for public health.